2013
DOI: 10.1111/clr.12229
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric osteotomy for the placement of titanium implants in rabbits: histomorphometry study

Abstract: Piezoelectric osteotomy allowed bone formation for osseointegration of titanium implants, was not associated with bone necrosis, and provided results similar to those of the conventional technique. The piezoelectric technique can be considered a viable alternative in dental implantology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…Moreover, the BIC ratio did not differ between the two groups, implying that osseointegration was properly achieved in both groups. Compared to other studies, the BV/TV ratio was lower (32.92% by Kfouri et al [ 29 ], 28.66% by Barak et al [ 30 ] and 26.28% by Al-Mahalawy et al [ 31 ]), and the BIC ratio was similarly measured (52.87% by Al-Mahalawy [ 31 ]). Although BV/TV ratio was lower than other researches due to the fact that, when setting the range for measuring the BV/TV ratio, the TV range was broadened, it is meaningful in that there was no significant difference between the two groups within the present study, which means similar bone volume was gained.…”
Section: Discussioncontrasting
confidence: 50%
“…Moreover, the BIC ratio did not differ between the two groups, implying that osseointegration was properly achieved in both groups. Compared to other studies, the BV/TV ratio was lower (32.92% by Kfouri et al [ 29 ], 28.66% by Barak et al [ 30 ] and 26.28% by Al-Mahalawy et al [ 31 ]), and the BIC ratio was similarly measured (52.87% by Al-Mahalawy [ 31 ]). Although BV/TV ratio was lower than other researches due to the fact that, when setting the range for measuring the BV/TV ratio, the TV range was broadened, it is meaningful in that there was no significant difference between the two groups within the present study, which means similar bone volume was gained.…”
Section: Discussioncontrasting
confidence: 50%
“…Burs/drills vs piezotomes: With moderate to strong evidence (EL: 1,3; Table 1) and consecutive substantial clinical impact piezotomes seem to provide an improved bonehealing, proved on molecular-biologic, micromorphologic and histologic level in vivo, when compared to rotary instruments. Furthermore, a superior soft-tissue-preservation is reported compared to drills and burs [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Group 3 (Experimental Studies In Vivo)mentioning
confidence: 99%
“…Few in vivo studies in the literature have conducted an evaluation of the histological aspects after the use of piezoelectric instruments in comparison with the conventional rotary cutting system, when preparing sites for implants [21][22][23][24] . It is important to emphasize that a direct comparison between the results of the present study and other, earlier studies is hindered by virtue of the different materials and methodologies employed and the distinct experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there was no significant difference between the area of contact between bone and implant, however this area was significantly smaller in the group of conventional cutting instruments at 7 and at 14 days. At the end of the study, after 28 days, the authors concluded that there was no difference between the piezoelectric and conventional instruments 24 . In another study previously carried out on beagles, Bengazi et al 22 also found that osseointegration of implants is possible if the sites are prepared using conventional drill cutters with copious irrigation or by means of piezoelectric surgery.…”
mentioning
confidence: 90%
See 1 more Smart Citation